If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -20 = 2x + -40 Reorder the terms: -20 + x = 2x + -40 Reorder the terms: -20 + x = -40 + 2x Solving -20 + x = -40 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -20 + x + -2x = -40 + 2x + -2x Combine like terms: x + -2x = -1x -20 + -1x = -40 + 2x + -2x Combine like terms: 2x + -2x = 0 -20 + -1x = -40 + 0 -20 + -1x = -40 Add '20' to each side of the equation. -20 + 20 + -1x = -40 + 20 Combine like terms: -20 + 20 = 0 0 + -1x = -40 + 20 -1x = -40 + 20 Combine like terms: -40 + 20 = -20 -1x = -20 Divide each side by '-1'. x = 20 Simplifying x = 20
| x+6=x+9 | | 0=3.4-0.17z | | 0.3(2y-12)-0.5(y-20)=3.4 | | 11-y=11 | | -9-7x= | | 8x-3=87-2x | | 0.07z=-0.72-5(0.3z-1.4) | | m/7-9=8 | | 9a+12=7a+9 | | 0-y=111 | | 250+t=141 | | 56ty-11=247 | | 200-3y-4x=0 | | 8.1-0.6t=7.2 | | 7(2x+10)=6x+26+6x+4 | | a-95=25 | | gcf=42x+28y | | b-5+0.2b=-0.2 | | -8(7)+y=4 | | x^5-3x^4-x^3+3x^2=f(x) | | 2/3+3x+1/4=5/3 | | -8(3)+y=4 | | 3.2x-0.88+1.2=0 | | -8(-2)+y=4 | | 2(5x+4)+2=60 | | 4g-8=-20 | | X*2+5x+3=0 | | 2+3(5+5v)=62 | | 42x+28y=gcf | | -2(3y-4)-y=-4(y-2) | | 3(3x+2)=6(2x-3) | | 9x+3=7x-19 |